TOPSIS Technique of MCDM under Cubic Intuitionistic Fuzzy Soft Set Environment - Saqlain, Muhammad; Imran, Raiha; Hassan, Sabahat (Scientific Inquiry and Review, 2023)
A powerful tool for dealing with ambiguity, attributive values, fuzziness, and inconsistency is the cubic intuitionistic fuzzy soft set. In this paper, multi-criteria group decision-making (MCGDM) technique called extended TOPSIS based on distance and similarity measures is presented. Furthermore, a real-world problem is resolved by applying CIFS-set to support the theoretical visualization. Arguably, the proposed technique works well and has practical uses.